The outstanding performance of the administrators of the national centers for the care of specialized sports talent in Iraq - م.م. هدى محمد سليمان (الرياضة المعاصرة)
The research aims to identify the reality of achieving the distinguished performance of the administrators of the National Center for the care of specialized sports talent in Iraq and the possibility of exerting various efforts to take care of talented athletes in order to reach Iraqi sports to the stage of high achievement. The research sample (116) was supervisor of the sports activities of the centers of Baghdad and governorates for 2018 The study sample was chosen in a deliberate manner for the administrators of the national centers for the care of sports talent. The descriptive method was used in the survey method to fit the study. The statistical bag was used to extract the results. Excellence research sample and the researcher recommended the inclusion of people with efficiency and competence of the work to create the right environment for continuous improvement and provide all the needs that enables administrators to exercise their work efficiently and effectively and to create creativity and motivate him.